Grit - "Duckworth, Angela" (London, 2016)
In this must-read for anyone seeking to succeed, pioneering psychologist Angela Duckworth takes us on an eye-opening journey to discover the true qualities that lead to outstanding achievement. Winningly personal, insightful and powerful, Grit is a book about what goes through your head when you fall down, and how that ? not talent or luck ? makes all the difference.
Keywords: Perseverance